RISK ASSESSMENT OF LIQUID CO₂ PRODUCTION USING HAZOP IN THE FERTILIZER INDUSTRY - RINY YOLANDHA PARAPAT; ABEL ASHA MAHENDRA, DIYAS YASYA SYAHWALNA (ADISAM PUBLISHER, 2025)
Risk identification and analysis are crucial aspects of process safety management in the chemical industry. This study applies the Hazard and Operability Study (HAZOP) method to identify potential hazards and operability issues in. The HAZOP method involves decomposing the system into nodes and applying guiding keywords to stimulate deviations from design parameters and normal operations. Each identified deviation is then evaluated to determine potential causes, consequences, and recommendations for mitigation actions. This analysis aims to provide a comprehensive understanding of the risks that may arise, including risks to safety, health, the environment, and financial losses. The results of this HAZOP study are expected to be the basis for developing effective risk control measures, improving system design, and developing safer operating procedures, thereby contributing to incident prevention and improving overall safety performance